VD_FINDINFO HC / 2013 / 560 vom 27. September 2013 - VD Tribunal cantonal (2013)
MESURE PROVISIONNELLE, SUPPRESSIONEN GÉNÉRAL, DÉCISION SUR FRAIS, DÉPENS | 29 al. 2 Cst., 104 al. 3 CPC (CH), 106 al. 1 CPC (CH), 263 CPC (CH)